Luminescence and Judd-Ofelt analysis of gallium aluminum gadolinium yttrium borate scintillating glass doped with Dy3+. (October 2022) - Borisut, P.; Insiripong, S.; Limkitjaroenporn, P.; Meejitpaisan, P.; Kaewnuam, E.; Chaipaksa, W.; Rajaramakrishna, R.; Kim, H.J.; Kaewkhao, J.
Abstract: In this work, Dy 3+ :B2 O3 –Ga2 O3 –Al2 O3 –Gd2 O3 –Y2 O3 glasses system were prepared by melt quenching technique. The physical, chemical groups, optical, photoluminescence and radioluminescence properties of glasses were investigated. The density and refractive index tended to increase with increasing Dy2 O3 concentration. The Dy 3+ doped glasses absorbed photon in UV, VIS and NIR region in the absorption spectra. For photoluminescence study, the 276 and 351 nm wavelength owned the strong excitation peak, so they were used to measure the emission spectra. The main emission peak of Dy 3+ showed at 487 and 575 nm with 4 F9/2 → 6 H15/2, 13/2 transition due to both direct excitation and the Gd–Dy energy transfer. The luminescence lifetime of Dy 3+ was in the milliseconds order that shortened with adding Dy2 O3 content. The PL emission intensity at 100 K was around 1.48 times compared to its value at room temperature (∼300 K). The Judd-Ofelt theory was used to analyse the radiative properties of glass and its result performed the quantum efficiency around 63.75%. The X-rays induced optical luminescence represented the highest intensity in 0.50 mol% Dy2 O3 -doped glass similarly to the photoluminescence under 351 nm excitation. The X-rays scintillation efficiency of this glass is 14% compared with BGO crystal. The developed glass in this work owns the potential for X-rays detection material with integration mode usage, and is also interesting for white light source and laser medium applications. Highlights: New Dy 3+ doped glass for X-ray detection material. Strong luminescence properties under the Gd 3+ → Dy 3+ energy transfer. Glass with potential radiative properties, confirmed by Judd-Ofelt analysis.